Ultra-Processed Foods Elicit Higher Approach Motivation Than Unprocessed and Minimally Processed Foods - Lemos, Thayane C.; Coutinho, Guilherme M. S.; Silva, Laiz A. A.; Stariolo, Jasmin B.; Campagnoli, Rafaela R.; Oliveira, Leticia; Pereira, Mirtes G.; Mota, Bruna E. F.; Souza, Gabriela G. L.; Canella, Daniela S.; Khandpur, Neha; David, Isabel A. (Frontiers in Public Health, 2022)
Background: Ultra-processed foods (UPF) are becoming extensively available in the food environments. UPF are industrial formulations that are designed to maximize palatability and consumption through a combination of calorie-dense ingredients and chemical additives. UPFs are also aggressively marketed, which may make them more attractive than unprocessed/minimally processed foods (UMPF). Since consumers’ purchase decisions are guided by food-evoked emotions, we aimed to provide evidence that UPF visual cues trigger higher emotional responses and approach motivation than UMPF visual cues, with potential impacts on individuals' intention to consume the UPF over the UMPF. Methods: Participants (n= 174; 144 women; mean age = 20.7 years; standard deviation = 4.35) performed two tasks. In the first task, 16 pictures of foods (8 UPF and 8 UMPF), and 74 pictures from other affective categories, were presented. After viewing each picture, the participants rated it along two basic dimensions of emotion through the Self-Assessment Manikin scale: pleasantness and arousal. In the second task, the participants viewed the same food pictures, and they rated their intention to consume the foods depicted in the pictures. Each picture was plotted in terms of its mean pleasantness and arousal ratings in a Cartesian plane, which resulted in an affective space. Results: Pictures of UPF and UMPF were positioned in the upper arm of the boomerang-shaped affective space that represents approach motivation. Pictures containing UPF triggered higher approach motivation and intention to consume than pictures containing UMPF. We also found a stronger association between emotional responses and intention to consume UPF relative to UMPF. Conclusion: These results shed new light on the role of ultra-processed foods evoked emotions that contribute to less healthy and sustainable food environments.